THE EFFECTIVENESS OF FINGER PAINTING GAMES TO DEVELOP SCIENTIFIC LITERACY IN EARLY CHILDREN: LITERATURE REVIEW - Eviani Masruroh; Rachma Hasibuan (Indonesian Journal of Education (INJOE), 2024)
Finger painting is an activity in science learning that can develop early childhood science literacy. However, the effectiveness of using finger painting is influenced by several factors. This study aims to identify and analyze factors that influence the effectiveness of using finger painting in developing early childhood science literacy. Based on a literature review, there are four main factors that can influence the effectiveness of using finger painting, namely: (1) teacher readiness in designing and implementing finger painting activities that are appropriate to the characteristics of children, (2) availability of materials and tools that support activities, (3) integration of finger painting with other science learning activities, and (4) parental involvement in supporting and continuing activities at home. These factors are interrelated and have an important role in creating effective science learning through the use of finger painting. The findings of this study can be a reference for teachers and related parties in designing and implementing finger painting as a strategy to develop science literacy in early childhood